Patterns of short saphenous vein incompetence. (March 2013) - Qureshi, M I; Lane, T R A; Moore, H M; Franklin, I J; Davies, A H
The significance of short saphenous vein (SSV) reflux is an under-explored territory in chronic venous disease (CVD). We have examined the origin and significance of SSV reflux in primary and secondary CVD. While the natural history of SSV incompetence remains uncertain, its prevalence has been shown to approximate 3.5%, rising with progressing clinical venous insufficiency, and bears an association with lateral malleolar venous ulceration. The most common pattern of reflux extends throughout the SSV Patterns of incompetence in recurrent disease are highly variable, but SSV reflux may itself pose a risk for recurrence, in part due to the complex anatomy of the saphenopopliteal system. Further studies are required to delineate the impact of SSV reflux in secondary venous disease and deep venous incompetence.